An internet-based intervention with brief nurse support to manage obesity in primary care (POWeR+): a pragmatic, parallel-group, randomised controlled trial. Issue 10 (October 2016) - Little, Paul; Stuart, Beth; Hobbs, FD Richard; Kelly, Jo; Smith, Emily R; Bradbury, Katherine J; Hughes, Stephanie; Smith, Peter W F; Moore, Michael V; Lean, Mike E J; Margetts, Barrie M; Byrne, Chris D; et al.
Summary: Background: The obesity epidemic has major public health consequences. Expert dietetic and behavioural counselling with intensive follow-up is effective, but resource requirements severely restrict widespread implementation in primary care, where most patients are managed. We aimed to estimate the effectiveness and cost-effectiveness of an internet-based behavioural intervention (POWeR+) combined with brief practice nurse support in primary care. Methods: We did this pragmatic, parallel-group, randomised controlled trial at 56 primary care practices in central and south England. Eligible adults aged 18 years or older with a BMI of 30 kg/m 2 or more (or ≥28 kg/m 2 with hypertension, hypercholesterolaemia, or diabetes) registered online with POWeR+—a 24 session, web-based, weight management intervention lasting 6 months. After registration, the website automatically randomly assigned patients (1:1:1), via computer-generated random numbers, to receive evidence-based dietetic advice to swap foods for similar, but healthier, choices and increase fruit and vegetable intake, in addition to 6 monthly nurse follow-up (control group); web-based intervention and face-to-face nurse support (POWeR+Face-to-face [POWeR+F]; up to seven nurse contacts over 6 months); or web-based intervention and remote nurse support (POWeR+Remote [POWeR+R]; up to five emails or brief phone calls over 6 months). Participants and investigators were masked to group allocation at the point of randomisation; masking of participants was not possible after randomisation. The primary outcome was weight loss averaged over 12 months. We did a secondary analysis of weight to measure maintenance of 5% weight loss at months 6 and 12. We modelled the cost-effectiveness of each intervention. We did analysis by intention to treat, with multiple imputation for missing data. This trial is registered as an International Standard Randomised Controlled Trial, number ISRCTN21244703. Findings: Between Jan 30, 2013, and March 20, 2014, 818 participants were randomly assigned to the control group (n=279), the POWeR+F group (n=269), or the POWeR+R group (n=270). Weight loss averaged over 12 months was recorded in 666 (81%) participants. The control group lost almost 3 kg over 12 months (crude mean weight: baseline 104·38 kg [SD 21·11; n=279], 6 months 101·91 kg [19·35; n=136], 12 months 101·74 kg [19·57; n=227]). The primary imputed analysis showed that compared with the control group, patients in the POWeR+F group achieved an additional weight reduction of 1·5 kg (95% CI 0·6–2·4; p=0·001) averaged over 12 months, and patients in the POWeR+R group achieved an additional 1·3 kg (0·34–2·2; p=0·007). 21% of patients in the control group had maintained a clinically important 5% weight reduction at month 12, compared with 29% of patients in the POWeR+F group (risk ratio 1·56, 0·96–2·51; p=0·070) and 32% of patients in the POWeR+R group (1·82, 1·31–2·74; p=0·004). The incremental overall cost to the health service per kg weight lost with the POWeR+ interventions versus the control strategy was £18 (95% CI −129 to 195) for POWeR+F and –£25 (−268 to 157) for POWeR+R; the probability of being cost-effective at a threshold of £100 per kg lost was 88% and 98%, respectively. No adverse events were reported. Interpretation: Weight loss can be maintained in some individuals by use of novel written material with occasional brief nurse follow-up. However, more people can maintain clinically important weight reductions with a web-based behavioural program and brief remote follow-up, with no increase in health service costs. Future research should assess the extent to which clinically important weight loss can be maintained beyond 1 year. Funding: Health Technology Assessment Programme of the National Institute for Health Research.